Handling the shortage of nurses in Germany: Opportunities and challenges of recruiting nursing staff from abroad - Emilia Reiff; Christel Gade; Susanne Böhlich (IUBH Internationale Hochschule, 2020)
The lack of qualified nurses has been a burden on the German health care system for many years. Due to the important role of nurses in health services, there are increasing attempts to address the shortage of staff by recruiting professionals from abroad. To alleviate the shortage of skilled labour in general, the German government passed a new law in 2020 on the immigration of skilled workers from outside the European Union to take up work in Germany (Fachkräfteeinwanderungsgesetz). Whether recruiting nurses from abroad is a viable or sufficient strategy needs to be evaluated. In our case, a selection of participants in the healthcare sector, hospital managers, staffing agencies and foreign nursing staff were interviewed. Although foreign professionals are perceived to make a significant contribution to mitigate the tight staffing situation, serious obstacles have been identified. In addition, data collected and analysed showed, that recruitment of foreign nursing staff still accounts for a small number of nurses. Even though it helps, it cannot substitute changes in the German system and workforce attractiveness itself. Especially, since nurses from abroad have similar work expectations as Germans do. The challenges for foreign nursing staff relate mainly to administrative hurdles, language barriers and social integration, especially cultural issues, the latter having also emerged as the key factors for long-term retention. Furthermore, the Global Code of Conduct of the WHO prohibits recruiting from countries which themselves already suffer from a shortage of skilled workers or have a similar demographic development as Germany. Also recruitment from abroad should not postpone necessary reforms in the German nursing sector. Therefore, recruiting foreign nurses is not the only strategy against the nursing shortage. Only a mix of different measures will lead to long-term success. The study provides insights into the feasibility and sustainability of international recruitment, not disregarding the complexity of the underlying reasons for the nursing shortage and is, therefore, relevant for scientists and practitioners alike.
Keywords: 650; nursing shortage; foreign nurses; professionals from abroad; obstacles to international recruitment; professional recognition; workplace integration; long-term retention